Sex Differences in the Outcomes of Cryoablation for Atrial Fibrillation - Hermida, Alexis; Burtin, Jacqueline; Kubala, Maciej; Fay, Floriane; Lallemand, Pierre-Marc; Buiciuc, Otilia; Lieu, Audrey; Zaitouni, Mustafa; Beyls, Christophe; Hermida, Jean-Sylvain (Frontiers in Cardiovascular Medicine, 2022)
Background: The literature data on the outcomes of radiofrequency catheter ablation for atrial fibrillation (AF) in women are contradictory. Aim: To determine and compare the outcomes and complications of cryoballoon pulmonary vein isolation (cryo-PVI) in men vs. women, and to identify predictors of atrial tachyarrhythmia (ATa) recurrence. Methods: We included all consecutive patients having undergone cryo-PVI for the treatment of symptomatic AF in our center since 2012. Peri-operative complications were documented. All patients were prospectively monitored for the recurrence of ATa, and predictors were assessed. Results: A total of 733 patients were included (550 men (75%) and 183 (25%) women). Paroxysmal AF was recorded in 112 (61%) female patients and 252 male patients (46%; p<0.001). Female patients were older (p<0.001) and had a greater symptom burden (p=0.04). Female patients were more likely to experience complications (p=0.02). After cryo-PVI for paroxysmal AF, 66% of the female patients and 79% of the male patients were free of ATa at 24 months (p=0.001). Female sex was the only independent predictive factor for ATa recurrence (hazard ratio [95% confidence interval] = 1.87 [1.28;2.73]; p=0.001). After cryo-PVI for non-paroxysmal AF, 37% of the male patients and 39% of the female patients were free of ATa at 36 months (p=0.73). Female patients were less likely than male patients to undergo repeat ablation after an index cryo-PVI for non-paroxysmal AF (p=0.019). Conclusion: A single cryo-PVI procedure for paroxysmal AF was significantly less successful in female patients than in male patients. Overall, the complication rate was higher in women than in men.